ANALYSIS OF THE VALUE CHAIN ​​OF MACA - López R, Juan Carlo (2001)
Today our country is facing a concrete, real and growing problem. This challenge is called: GLOBALIZATION. If we do not give added value to our exports will deepen our problem even more ...